Juego libre y el desarrollo de la motricidad gruesa en niños y niñas de cuatro y cinco años de la institución educativa inicial N° 657 Niños del Saber, distrito de Punchana 2022 - Ayache Taminchi, Mary Isabel (2025)
An investigation was carried out with the objective of determining the relationship between free play and the development of gross motor skills in children from the Initial Educational Institution No. 657 Children of Knowledge, Punchana district, 2022. The study was correlational, with a non-experimental design and a descriptive approach. The population and sample consisted of 142 enrolled children, and an observation guide validated by experts was applied as an instrument. The results indicated that 80.3% of the children managed to develop their gross motor skills, while 77.5% performed free play constantly, evidencing a statistically significant relationship between both variables. The statistical analysis (tc = 13.242; p < 0.05) allowed us to accept the research hypothesis (H1), confirming that free play is significantly related to the development of gross motor skills in 4 and 5 year old children.